The Relationship of Good Governance with Organizational : Commitment of Benghazi Municipality Office. - العبار د. بشير محمد (Dirasat in Economics and Business, 2022)
The study aimed to identify the level of application of the standards of good governance: (transparency, justice, participat-ion, accountability, rule of law, strategic vision) and its relation-ship to the organizational comm-itment of the municipality of Benghazi. The data, and the stu-dy population may have consist-ed of all (65) senior, middle and executive management manage-rs. The researcher studied it com-pletely using the comprehensive inventory method, and the statist-ical packages program (SPSS) was also used in analyzing the data, and the study reached many results, the most important of which are the level of applicat-ion of the standards of good gov-ernance and the degree of orga-nizational commitment were mo-derate, and the existence of a strong positive relationship bet-ween the application of the coll-ective standards of good govern-ance and organizational commi-tment, and the existence of a strong positive relationship bet-ween the application of the foll-owing standards of good gov-ernance: (transparency, fairness, and participation) and organiza-tional commitment, as well as the existence of a relationship. There is a weak positive between the application of the standard (stra-tegic vision) and organizational commitment, and the study pres-ented a set of recommendations that it is hoped that the Contr-ibute to enhancing the level of application of standards of good governance, and improving the degree of organizational comm-itment to the Benghazi munic-ipality's office.